TANTANGAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH MENENGAH PERTAMA (SMP) - Fitri Hartawati; Karim, Maizar (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Over time, the challenges and roles carried out by teachers will certainly change, one of which is the development in the field of technology which also plays a role and can affect these changes. Especially when referring to various policies in the existing and latest curriculum, of course this is one of the interesting things to discuss. Therefore, the author's aim to be conveyed in this paper is to discuss the challenges and role of the teacher himself specifically in dealing with the use of the independent learning curriculum which is the latest curriculum and will be implemented later. Then related to the data sources used are various forms of literature that are certainly related to the theme, be it in the form of books, articles, journals, and other sources of writing on the internet. For the writing itself, the author uses the library study method or library research by searching and collecting relevant data sources, then filtering the sources that have been collected so that the most relevant sources can be found with the theme to be studied or raised, then making conclusions and recording various important things from existing sources, and only then will it be implemented in the form of writing.